Energy-Efficient Precoder Design for MIMO Wiretap Channels - Zhang, Haiyang; Huang, Yongming; Li, Shidang; Yang, Luxi (IEEE communications letters, 2014)
In this letter, we study energy-efficient precoder design in a three-node MIMO wiretap channel. Different from previous works in this area that mainly focus on secrecy rate maximization or power minimization problems, here, we aim to maximize the energy efficiency (EE) of the system subject to the secret rate and transmit power constraints, which is a nonconvex optimization and hard to tackle. To solve it, we first transform it into an equivalent parameterized polynomial subtractive form and then approximate the nonconvex equivalent problem into a convex optimization problem by means of Taylor series expansion. Based on that, an iterative algorithm with proved convergence is proposed, and this algorithm is also extended to an imperfect-channel-state-information case. Numerical results show that the proposed algorithm outperforms traditional design methods in terms of EE.